Analysis of particle dynamics, event horizon, and thermodynamic properties of black holes in the Ghasemi-Nodehi-Bambi metric - Siagian, Ruben Cornelius (Universitas Syiah Kuala, 2025)
Black holes, as complex astrophysical objects, are strongly influenced by their metric parameters. This research focuses on the Ghasemi-Nodehi-Bambi (G-N-B) metric, an extension of the Kerr solution, which introduces additional parameters to more accurately describe the properties of black holes. The research investigates the impact of parameter variations in the G-N-B metric on black hole thermodynamics, particle dynamics, and event horizon structure. Analytical and numerical methods are applied to examine the quadratic equations governing event horizons, particle motion, and black hole temperature and entropy. The research explores the variation of parameters (M) and (a) within a certain range to evaluate their influence on the gravitational distribution and the effect of frame attraction. The distribution of (M) values was visualized on a logarithmic scale to highlight the sensitivity of the system to parameter changes. The study found that variations in the G-N-B metric parameter significantly affect the event horizon, with the likelihood of extreme black holes or naked singularities forming depending on the discriminant of the quadratic equation. Particle motion is affected by parameters (M) and (a), which alter the gravitational field and orbital stability. The black hole temperature and entropy show significant changes: an increase in (M) increases gravity and surface temperature, while an increase in (a) decreases temperature due to rotational effects. The research improves the understanding of black holes beyond the Kerr model, especially in terms of black hole thermodynamics and time-space structure.